FAKTOR RISIKO KEJADIAN ABORTUS DI RSUD DR. CHASAN BOESOIRIE TERNATE PROVINSI MALUKU UTARA - Hubaya, Sitti; Arifin, M; Burhanuddin, Burhanuddin (Jurnal Kesehatan Poltekkes Ternate, 2015)
Abstract : This study aims to determine the risks of pregnancy outside marriage, contraception failure, socioeconomic status, history of abortion, and parity on the incidence of abortion in Hospital Dr.Chasan Boesoirie Ternate. The study design was a "Case Control Study", with oservasi unit consisting of a group of cases and controls.Sample size of 158 people that is the case group and the control group of 79 respondents 79 respondents were taken by purposive sampling.Data analysis was performed using univariate, bivariate odds ratio test and multivariate analysis with logistic regression. The results showed that the risk variabels on the incidence of abortion, namely: contraceptive failure OR = 3.57 (95% CI: 1,746 to7.307 ; p = 0.001), socioeconomic status OR =3.22, 95% CI:1.573 to2.249 ; p = 0.002), history OR = 2.60 (95% CI: 1.355 to 4.993 ; p = 0.006) and parity OR = 2.98 (95% CI: 1,502 to 5.933 ; p = 0.003). While the non-risk variabels on the incidence of abortion is pre-marital pregnancy OR = 1.43 (95% CI:0.437 to4.742 ; p=0,764).